BOKASHI AND LENGTH OF CUTTINGS IN THE VEGETATIVE PROPAGATION OF Pereskia aculeata Plum (ORA-PRO-NÓBIS) - Milene Silverio, Juliana; Correia Santos, Cleberton; Estevão Wilkomm, Venâncio; Roberto Bruschis Karas, Diogo; Vieira, Maria do Carmo; Heredia Zárate, Néstor Antonio (Revista Brasileira de Engenharia de Biossistemas, 2021)
There is little technical information on the factors that can influence the vegetative propagation of the Pereskia aculeata Plum. Thus, the aim this study was to know the effect of the length of cuttings and the use of bokashi in the propagation of P. aculeata. Three lengths of cuttings were evaluated: 15, 20 and 25 cm, without and with bokashi, under nursery with 50% shade. The cuttings were propagated in 500 mL plastic containers with substrate Dystrophic Red Latosol + Tropstrato (1: 1, v/v). Sprouts were evaluated weekly after the first sprouting, and at 60 days after cutting, whole seedlings were harvested. The highest sprouting percentage was 60% and the sprout velocity index of 0.8737 of the 20 cm cuttings, with bokashi. The highest number of sprout (6.12) and leaves (24.83) was observed in 25 cm cuttings, independent of use bokashi. The highest values root length (16.58 cm) and the production of fresh and dry mass sprouting (19.23 and 11.22 g, respectively) were in seedlings with cuttings of 25 cm. The addition of bokashi and cuttings 25 cm favored higher production of dry mass sprouts. Use of cuttings 25 cm contribute to the production of P. aculeata seedlings because they favor sprouting indicators, leaf area and physiological indices.